[Retracted]: SYSTEM SOFTWARE AT LABORATORY STAND „LIGHTS CONTROL ON THE BASIS OF PROGRAMMABLE LOGIC CONROLLER”: The article has been retracted due to a breach of ethical standards. The editorial board received a report that this work infringes on the copyrights of others. An investigation confirmed the validity of the report, resulting in the decision to retract the work. The evidence in the case is in the possession of the editorial board. The editorial board of the journal also declares that it has followed all procedures for checking the article for unethical practices before its publication in 2022. - Yesmakhanova, Laura; Dzhanuzakova, Raushan; Myrkalykov, Bauyrzhan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The article is concerned with the issues of practical utilization of controllers for automation in various technical fields as example Mitsubishi controllers of MELSEC FX1N and FX3U series. Any task, which requires the utilization of electrical control devices, is easy to solve by means of usage of programmable logic controllers. By using software with controllers programming package GX Developer, user has the possibility to program the controller or input changes into existing program. The Laboratory Stand was developed for effective learning of controller programming in LD language.